PARAPHIMOSIS IN A PUBERTAL PIG AND ITS SUCCESSFUL CORRECTION - S. Prakash; P.V. Jeevika; S. Raja; S. Satheshkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A Large White Yorkshire male pubertal pig was presented with the history of sustained protrusion of penis for about six hours. Edema of the protracted penis was reduced. Manual repositioning and retension of glans penis into preputial cavity was carried out successfully. There was no recurrence.